Pengaruh Promosi Dan Harga Terhadap Minat Beli Yang Dimediasi Oleh Kepercayaan Pada Pelanggan Indihome Di Kota Palangka Raya (Studi Emperis Pada PT.Telkom Provinsi Kalimantan Tengah) - Achmad Mustofa Nur; Saladin Ghalib; Setio Utomo (Universitas Lambung Mangkurat, 2020)
Indihome is a new product launched by PT Telkom. It is a challenge for PT This study aims to test the influence of Promotion (X1)and Price(X2) of the Interests Disire (Y) that is mediated by the Trust (Z) on the Customer Indihome in the city of Palangkaraya.Samples were taken as many as85 Indihome Customers in Palangka Raya Cityby using the structural equation model (Structural Equation Model). Data were collected using questionnaire while data analysis usingStuctural Equation Modeling (SEM) with Smart Partial Least Square (Smart PLS) software version 2.0 M3.The test results prove that 1) Promotion has significant effect to Buy Disire Indihome in Palangkaraya City, 2)Price has significant effect to Buy Disire of Indihome Customers in Palangka Raya City, 3)Promotion have significant influence to Indihome Customer Trust in Palangkaraya City, 4)Price have significant influence to Indihome Customer Confidence in Palangkaraya City, 5)Trust has significant influence to Buy Disire of Indihome Customers in Kota Palangka RayaKeywords: Promotion, Price, Trust, Buying Disire